A Systematic Review on Antimicrobial Pharmacokinetic Differences between Asian and Non-Asian Adult Populations - Eko Setiawan; Menino Osbert Cotta; Jason A. Roberts; Mohd Hafiz Abdul-Aziz (MDPI AG, 2023)
While the relevance of inter-ethnic differences to the pharmacokinetic variabilities of antimicrobials has been reported in studies recruiting healthy subjects, differences in antimicrobial pharmacokinetics between Asian and non-Asian patients with severe pathologic conditions require further investigation. For the purpose of describing the potential differences in antimicrobial pharmacokinetics between Asian and non-Asian populations, a systematic review was performed using six journal databases and six theses/dissertation databases (PROSPERO record CRD42018090054). The pharmacokinetic data of healthy volunteers and non-critically ill and critically ill patients were reviewed. Thirty studies on meropenem, imipenem, doripenem, linezolid, and vancomycin were included in the final descriptive summaries. In studies recruiting hospitalised patients, inconsistent differences in the volume of distribution (Vd) and drug clearance (CL) of the studied antimicrobials between Asian and non-Asian patients were observed. Additionally, factors other than ethnicity, such as demographic (e.g., age) or clinical (e.g., sepsis) factors, were suggested to better characterise these pharmacokinetic differences. Inconsistent differences in pharmacokinetic parameters between Asian and non-Asian subjects/patients may suggest that ethnicity is not an important predictor to characterise interindividual pharmacokinetic differences between meropenem, imipenem, doripenem, linezolid, and vancomycin. Therefore, the dosing regimens of these antimicrobials should be adjusted according to patients' demographic or clinical characteristics that can better describe pharmacokinetic differences.